2017
DOI: 10.1186/s41239-017-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of the meaning and value of analytics in New Zealand higher education institutions

Abstract: This article presents the current perceptions on the value of analytics and their possible contribution to the higher education sector in New Zealand. Seven out of eight research-intensive public universities in New Zealand took part in the study. Participants included senior management and those who have some role associated with decisionmaking within higher education (N = 82). The study found inconsistent understanding of the meaning of analytics across participants. In particular, three forms of perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Staff were little better informed: 39% of staff in a global online survey of 121 academics (Drachsler & Greller, 2012) did not know or were unsure about whether they had an ethics committee and guidelines in place for the use of student data for research and 12% of senior staff at New Zealand universities (Mahroeian et al, 2017) did not know if their university was using learning analytics or not. A survey of 22 Australian universities (West et al, 2016) showed that only four universities had informed all relevant parties (by their own definition) about the use and impact of learning analytics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Staff were little better informed: 39% of staff in a global online survey of 121 academics (Drachsler & Greller, 2012) did not know or were unsure about whether they had an ethics committee and guidelines in place for the use of student data for research and 12% of senior staff at New Zealand universities (Mahroeian et al, 2017) did not know if their university was using learning analytics or not. A survey of 22 Australian universities (West et al, 2016) showed that only four universities had informed all relevant parties (by their own definition) about the use and impact of learning analytics.…”
Section: Resultsmentioning
confidence: 99%
“…Students acknowledged the potential for data analytics to improve the student experience, including through minimizing isolation, helping students who find it difficult to ask for help, and reaching students with different learning styles (Heath & Leinonen, 2016; Roberts et al, 2016). Both staff and students recognized that data analytics can: help students learn more effectively (Corrin et al, 2013; Heath & Leinonen, 2016; Howell et al, 2018; Kammer, 2015; Knight et al, 2016; Mahroeian et al, 2017), provide helpful feedback to which students can respond (Corrin et al, 2013; Heath & Leinonen, 2016; Howell et al, 2018; Kammer, 2015; Roberts et al, 2016), and identify “at–risk” students (Corrin et al, 2013; Heath & Leinonen, 2016; Howell et al, 2018; Knight et al, 2016; Mahroeian et al, 2017; Roberts et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Value of the data Demographic data provided in this article will encourage empirical research and the adoption of data analytics in understanding the trends in enrollment of undergraduates in higher education, especially in developing countries [1] , [2] , [3] , [4] , [5] . Unrestricted access to these demographic data will give executives, management, and policy makers in higher education useful insights for better decision-making [6] , [7] .…”
mentioning
confidence: 99%
“…Demographic data provided in this article will encourage empirical research and the adoption of data analytics in understanding the trends in enrollment of undergraduates in higher education, especially in developing countries [1] , [2] , [3] , [4] , [5] .…”
mentioning
confidence: 99%